Answer:
−2(−9x+5)−4x=2(x−5)−4
Step 1: Simplify both sides of the equation.
−2(−9x+5)−4x=2(x−5)−4
(−2)(−9x)+(−2)(5)+−4x=(2)(x)+(2)(−5)+−4(Distribute)
18x+−10+−4x=2x+−10+−4
(18x+−4x)+(−10)=(2x)+(−10+−4)(Combine Like Terms)
14x+−10=2x+−14
14x−10=2x−14
Step 2: Subtract 2x from both sides.
14x−10−2x=2x−14−2x
12x−10=−14
Step 3: Add 10 to both sides.
12x−10+10=−14+10
12x=−4
Step 4: Divide both sides by 12.
12x
12
=
−4
12
x= -1/3
Step-by-step explanation:
Good luck! Hope this helps! <3
Answer:
Step-by-step explanation:
Divide both sides by -3, and replace
with
. Then
![-3x^4+27x^2+1200=0\iff y^2-9y-400=0](https://tex.z-dn.net/?f=-3x%5E4%2B27x%5E2%2B1200%3D0%5Ciff%20y%5E2-9y-400%3D0)
Factorize the quadratic in
to get
![y^2-9y-400=(y+16)(y-25)=0\implies y=-16,y=25](https://tex.z-dn.net/?f=y%5E2-9y-400%3D%28y%2B16%29%28y-25%29%3D0%5Cimplies%20y%3D-16%2Cy%3D25)
which in turn means
![x^2=-16,x^2=25](https://tex.z-dn.net/?f=x%5E2%3D-16%2Cx%5E2%3D25)
But
for all real
, so we can ignore the first solution. This leaves us with
![x^2=25\implies x=\pm\sqrt{25}=\pm5](https://tex.z-dn.net/?f=x%5E2%3D25%5Cimplies%20x%3D%5Cpm%5Csqrt%7B25%7D%3D%5Cpm5)
If we allow for any complex solution, then we can continue with the solution we ignored:
![x^2=-16\implies x=\pm\sqrt{-16}=\pm i\sqrt{16}=\pm4i](https://tex.z-dn.net/?f=x%5E2%3D-16%5Cimplies%20x%3D%5Cpm%5Csqrt%7B-16%7D%3D%5Cpm%20i%5Csqrt%7B16%7D%3D%5Cpm4i)
Answer:
It is not
Step-by-step explanation:
It is not because this is an exponential function
y=x^2
1^2=1
2^2=4
3^2=9
4^2=16
The graph crosses the x axis 3 times so there are 3 roots.
B